The impact of Covid-19 related school policies on students in their final high school years - Malte Sandner; Silke Anger; Hans Dietrich; Sarah Bernhard; Alexander Patzina (ZBW - Leibniz Information Centre for Economics, 2021)
This paper sheds light on the impact of the COVID-19 policy measures on a wide set of career expectations, occupational beliefs, and well-being of high-school students in their final grades. For this purpose, we use a unique panel data collection, which surveyed around 6,000 students in their final or pre-final high school year in Germany. We have for the same students information about outcomes in three waves, before the outbreak of the Covid-19 pandemic (fall 2019), close after (spring 2020), and several months after (fall 2020), when the COVID-19 incidences were high again. The second survey wave includes students who responded to the survey before as well as students who participated after the school closures. We exploit this variation to apply a difference-in-differences design using students who answered the survey before the school closures as control group. We find only small effects of the pandemic on career decisions and occupational beliefs in the short and the long run. However, life satisfaction and mental-well-being strongly decreases in the ongoing pandemic.
Keywords: I24; I14; I31; 330; Covid-19; High School Students; Mental Health; Expectations; career planning